Z-type heterojunction semiconductor material and preparation method and application thereof

The Z-type heterojunction semiconductor material addresses low charge separation efficiency in photocatalysis by forming a heterojunction with BaTiO3-x on ZnIn2S4, improving photocatalytic activity and redox ability through enhanced charge separation and migration.

CN119186598APending Publication Date: 2024-12-27GANNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411379878.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing photocatalytic technologies face low charge separation efficiency due to insufficient light capture and fast recombination of photogenerated carriers, limiting their practical application, and traditional ZnIn2S4-based heterojunction photocatalysts suffer from separate reduction and oxidation processes affecting redox ability.

Method used

A Z-type heterojunction semiconductor material is developed by coating BaTiO3-x on ZnIn2S4, forming a heterojunction structure with optimized particle sizes and molar ratios, and a specific preparation method involving calcination and chemical reactions to enhance charge separation and migration.

Benefits of technology

The Z-type heterojunction semiconductor material improves photogenerated charge separation and migration, enhancing photocatalytic activity and redox ability, making it suitable for piezoelectric photocatalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186598A_ABST
    Figure CN119186598A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysts, and particularly relates to a Z-type heterojunction semiconductor material and a preparation method and application thereof. According to the invention, ZnIn2S4 is used as a matrix material, a built-in electric field and non-contact external field strategy is adopted, spatial separation and migration of a photon-generated carrier are enhanced, a directional charge transfer channel and a photooxidation reduction targeting active site are constructed, the separation efficiency of the photon-generated carrier is improved to the greatest extent, and the photoelectric conversion efficiency is improved. And constructing to obtain the Z-type heterojunction semiconductor material with strong oxidation-reduction capability. The invention also provides application of the Z-type heterojunction semiconductor material in the scheme or the Z-type heterojunction semiconductor material obtained by the preparation method in the scheme as a piezoelectric photocatalyst. The Z-type heterojunction semiconductor material provided by the invention is good in photo-generated charge separation capacity and transmission efficiency and high in photocatalytic activity, can be used as a piezoelectric photocatalyst, and is wide in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a Z-type heterojunction semiconductor material and a preparation method and application thereof. Background Art

[0002] The free carriers and free radicals generated by photocatalytic technology in practical applications only work under strong light intensity, such as ultraviolet lamps, 300W xenon lamps or high-intensity sunlight, which limits the practical application of photocatalytic technology. In order to improve the efficiency of photocatalysis, scientists have been committed to exploring advanced photocatalysts with excellent light capture ability, high carrier separation efficiency and high catalytic reaction activity in the past few decades. However, due to its low photogenerated charge separation efficiency, the efficiency of photocatalytic technology is still not high.

[0003] In addition to solar energy, mechanical energy can also be converted into chemical energy using piezoelectric semiconductor materials. Similar to photocatalysis, the use of piezoelectric charges caused by mechanical vibration can also promote catalytic redox reactions. Piezocatalysis uses the piezoelectric effect of piezoelectric materials to generate an internal electric field, promote the efficient separation of electron-hole pairs, and enable carriers to participate in redox reactions directly or by forming various active free radicals, thereby initiating the catalytic process. When piezoelectric materials are deformed under external stress, the non-zero dipole moment formed in the lattice accompanied by the transformation of the intrinsic crystal structure will produce a polarization potential, and then a piezocatalytic reaction will occur at the surface interface of the piezoelectric material. Therefore, by integrating piezoelectric, photoexcitation and semiconductor properties, the built-in electric field polarization induced by mechanical energy stimulation can be used as a flexible automatic valve to regulate the charge transfer pathway and promote the separation of photogenerated charges on the semiconductor surface. The combination of piezocatalysis and photocatalysis can effectively solve the problem of low charge separation efficiency by providing piezoelectric fields and photogenerated charges at the same time. Piezophotocatalysis can perfectly combine the advantages of piezocatalysis and photocatalysis to achieve efficient catalytic activity.

[0004] ZnIn2S4 is a semiconductor material with superior layered structure and suitable electronic band structure, but its utilization rate of visible light is insufficient, its specific surface area is low, and the recombination rate of photogenerated carriers is fast. These factors lead to the relatively low photocatalytic efficiency of ZnIn2S4. The researchers proposed to construct a ZnIn2S4-based heterostructure photocatalyst to meet the needs of light capture and charge carrier separation.

[0005] Traditional ZnIn2S4-based heterojunction photocatalysts can effectively enhance electron-hole separation, but since the reduction and oxidation processes occur separately on semiconductors with lower potentials, the redox ability of the photocatalyst is affected. Summary of the invention

[0006] The object of the present invention is to provide a Z-type heterojunction semiconductor material and a preparation method and application thereof. The Z-type heterojunction semiconductor material provided by the present invention has excellent piezoelectric photocatalytic reduction performance.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a Z-type heterojunction semiconductor material, comprising BaTiO 3-x and coated on the BaTiO 3-x The surface of ZnIn2S4; the BaTiO 3-x Forming a heterojunction structure with ZnIn2S4; the BaTiO 3-x The value range of x is 0.001~0.045.

[0009] Preferably, the value range of x is 0.005 to 0.040.

[0010] Preferably, the ZnIn2S4 and BaTiO 3-x The molar ratio is 12 to 15:1.

[0011] Preferably, the particle size of the ZnIn2S4 is 500-700 nm, and the BaTiO 3-x The particle size is 100~300nm.

[0012] The present invention also provides a method for preparing the Z-type heterojunction semiconductor material described in the above scheme, comprising the following steps:

[0013] (1) BaTiO3 and sodium borohydride are mixed and calcined in a protective atmosphere to obtain BaTiO 3-x ;

[0014] (2) The BaTiO 3-x The Z-type heterojunction semiconductor material is obtained by mixing with glycerol, zinc salt, indium salt, thioacetamide and water for chemical reaction.

[0015] Preferably, the calcination temperature is 400-500° C., and the calcination time is 1.5-3 hours.

[0016] Preferably, the BaTiO 3-x The molar ratio of Ba to zinc in the zinc salt is 15-17:100.

[0017] Preferably, the BaTiO 3-x The molar ratio of Ba to indium in the indium salt is 8:54-65.

[0018] Preferably, the BaTiO 3-x The mass ratio of thioacetamide to 1:2-3.

[0019] Preferably, the chemical combination reaction is carried out in an oil bath; the temperature of the chemical combination reaction is 75 to 85° C., and the insulation reaction time is 1.5 to 2.5 hours.

[0020] The present invention also provides the use of the Z-type heterojunction semiconductor material described in the above scheme or the Z-type heterojunction semiconductor material obtained by the preparation method described in the above scheme as a piezoelectric photocatalyst.

[0021] Preferably, the application comprises the following steps: adding a Z-type heterojunction semiconductor material to a reaction system to be catalyzed under ultrasonic conditions to carry out a piezoelectric photocatalytic reaction.

[0022] The present invention provides a Z-type heterojunction semiconductor material. 3-x @ZnIn2S4 heterojunction, BaTiO 3-x It is obtained by reducing BaTiO3 to form oxygen vacancies, which can effectively regulate the electronic structure of the material surface and enhance the electron enrichment effect. On the one hand, it can promote the material's absorption of visible light; on the other hand, it can change the material's charge transfer ability. The inner layer of BaTiO 3-x Photogenerated holes and electrons can be extracted from ZnIn2S4, which greatly improves the separation and migration rate of photogenerated carriers and realizes the spatial separation of redox sites. 3-x The piezoelectric effect generated by the components will form a polarization electric field under stress, further driving the photogenerated charges in BaTiO 3-x @ZnIn2S4 spatial separation on the heterojunction improves the BaTiO 3-x The extraction rate of photogenerated holes promotes the 3-x @The utilization rate of photogenerated electron-hole pairs in the ZnIn2S4 heterojunction has been improved, which has accelerated the catalytic reaction rate of surface photoredox.

[0023] The present invention also provides a method for preparing the Z-type heterojunction semiconductor material described in the above scheme. The present invention uses ZnIn2S4 as a matrix material, adopts a built-in electric field and a non-contact external field strategy, strengthens the spatial separation and migration of photogenerated carriers, constructs a directional charge transfer channel and a photoredox targeted active site, maximizes the separation efficiency of photogenerated carriers, and constructs a Z-type heterojunction semiconductor material with strong redox ability.

[0024] The present invention also provides the use of the Z-type heterojunction semiconductor material described in the above scheme or the Z-type heterojunction semiconductor material obtained by the preparation method described in the above scheme as a piezoelectric photocatalyst. The Z-type heterojunction semiconductor material provided by the present invention has good photogenerated charge separation ability and transmission efficiency, high photocatalytic activity, can be used as a piezoelectric photocatalyst, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 The BaTiO of Example 1 3-x SEM images of

[0027] Figure 2 is a SEM image of the Z-type heterojunction semiconductor material of Example 1;

[0028] Figure 3 is the ESR spectrum of oxygen vacancies (OVs);

[0029] Figure 4 The BaTiO of Example 1 3-x , ZnIn2S4 and BaTiO 3-x @XRD pattern of ZnIn2S4;

[0030] Figure 5 BaTiO 3-x @Piezoelectric catalytic degradation curve of ZnIn2S4 under different conditions. DETAILED DESCRIPTION

[0031] The present invention provides a Z-type heterojunction semiconductor material, comprising BaTiO 3-x and coated on the BaTiO 3-x The surface of ZnIn2S4; the BaTiO 3-x Forming a heterojunction structure with ZnIn2S4; the BaTiO 3-x The value range of x is 0.001~0.045.

[0032] In the present invention, the value range of x is preferably 0.005 to 0.040, and specifically can be 0.005, 0.010, 0.015, 0.020, 0.025, 0.030, 0.035 or 0.040.

[0033] In the present invention, the ZnIn2S4 and BaTiO 3-x The molar ratio of is preferably 12 to 15:1, specifically 12:1, 13:1, 13.5:1, 14:1 or 15:1.

[0034] In the present invention, the particle size of the ZnIn2S4 is preferably 500-700 nm, specifically 500 nm, 550 nm, 600 nm, 650 nm or 700 nm; the BaTiO 3-x The particle size is preferably 100 to 300 nm, specifically 100 nm, 150 nm, 200 nm, 250 nm or 300 nm.

[0035] The present invention also provides a method for preparing the Z-type heterojunction semiconductor material described in the above scheme, comprising the following steps:

[0036] (1) The BaTiO3 and sodium borohydride are mixed and calcined in a protective atmosphere to obtain BaTiO 3-x ;

[0037] (2) The BaTiO 3-x The Z-type heterojunction semiconductor material is obtained by mixing with glycerol, zinc salt, indium salt, thioacetamide and water for chemical reaction.

[0038] The present invention mixes BaTiO3 and sodium borohydride (referred to as the first mixture) and calcines them in a protective atmosphere to obtain BaTiO 3-x In the present invention, the preparation method of BaTiO3 is preferably: titanium dioxide, barium hydroxide and water are mixed (referred to as the second mixing) and subjected to a hydrothermal reaction to obtain BaTiO3.

[0039] In the present invention, the barium hydroxide is preferably barium hydroxide octahydrate; the mass ratio of titanium dioxide to barium hydroxide is preferably 16-20:380-400, specifically 16:380, 17:380, 18:380, 19:380, 20:380, 16:390, 18:390, 20:390, 16:400, 18:400 or 20:400.

[0040] In the present invention, the water is preferably deionized water; the mass ratio of the titanium dioxide to water is preferably 16-18:1000-1200, specifically 16:1000, 17:1000, 18:1000, 16:1100, 17:1100, 18:1100, 16:1200, 17:1200 or 18:1200.

[0041] In the present invention, the temperature of the hydrothermal reaction is preferably 180-200°C, specifically 180°C, 185°C, 190°C, 195°C or 200°C, and the insulation reaction time is preferably 36-48h, specifically 36h, 40h, 44h or 48h; the equipment for the hydrothermal reaction is preferably a polytetrafluoroethylene reactor.

[0042] In the present invention, after the hydrothermal reaction, the product is preferably pickled to neutrality (pH = 7) and then dried; the pickling reagent preferably includes hydrochloric acid and deionized water; the drying is preferably vacuum drying; the drying temperature is preferably 60-70°C, specifically 60°C, 63°C, 67°C or 70°C, the vacuum degree is preferably 130-135Pa, specifically 133Pa, and the heat preservation and drying time is preferably 20-36h, specifically 20h, 24h, 27h, 30h, 32h or 36h.

[0043] In the present invention, the mass ratio of BaTiO3 to sodium borohydride is preferably 2:3-4, specifically 2:3, 2:3.5 or 2:4. The present invention utilizes the reduction effect of sodium borohydride to form oxygen vacancies in BaTiO3.

[0044] In the present invention, the protective atmosphere is preferably nitrogen protection; the calcination temperature is preferably 400-500°C, specifically 425°C, 450°C, 475°C or 500°C; the insulation calcination time is preferably 1.5-3h, specifically 1.7h, 2h, 2.1h, 2.3h, 2.5h or 2.8h; the calcination equipment is preferably a tubular furnace.

[0045] In the present invention, after calcination, the product is preferably washed and then dried; the number of washings is preferably more than 3 times; the washings are preferably water washing and alcohol washing in sequence; the water used for water washing is preferably deionized water; the alcohol used for alcohol washing is preferably ethanol; the drying temperature is preferably 60-65°C, specifically 60°C, 62°C, 64°C or 65°C, and the heat preservation and drying time is preferably 20-30h, specifically 20h, 24h, 27h or 30h.

[0046] Obtaining BaTiO 3-x After that, the present invention converts the BaTiO 3-x The mixture is mixed with glycerol, zinc salt, indium salt, thioacetamide and water (referred to as the third mixture) to undergo a chemical reaction to obtain a Z-type heterojunction semiconductor material. In the present invention, the water is preferably deionized water; the pH value of the water is preferably 2 to 3, specifically 2.5; the BaTiO 3-x The mass ratio of the polyol to water is preferably 0.1:32 to 35, and specifically can be 0.1:32, 0.1:33, 0.1:34 or 0.1:35.

[0047] In the present invention, the volume ratio of water to glycerol is preferably 4-5:1, specifically 4:1, 4.5:1 or 5:1.

[0048] In the present invention, the zinc salt is preferably zinc chloride; the BaTiO 3-x The molar ratio of Ba to zinc in the zinc salt is preferably 15 to 17:100, specifically 15:100, 15.5:100, 16:100, 16.5:100 or 17:100.

[0049] In the present invention, the indium salt preferably includes one or both of indium trichloride and indium trichloride tetrahydrate; the BaTiO 3-x The molar ratio of Ba to indium in the indium salt is preferably 8:54-65, specifically 8:54, 7:50, 8:55, 8:58, 8:60, 8:62 or 8:65.

[0050] In the present invention, the BaTiO 3-x The mass ratio of thioacetamide to ZnIn2S4 is preferably 1:2-3, specifically 1:3, 1:2, 1:2.3, 1:2.5 or 1:2.7. The present invention utilizes thioacetamide to provide sulfur element to ZnIn2S4.

[0051] In the present invention, the third mixing is preferably stirring mixing followed by ultrasonic mixing; the power of the ultrasonic mixing is preferably 80-120 W, specifically 100 W, the frequency is preferably 40-60 kHz, specifically 50 kHz, and the mixing time is preferably 10-20 min, specifically 10 min, 15 min or 20 min.

[0052] In the present invention, the third mixture is preferably: BaTiO 3-x The mixture is premixed with water to obtain a premixed liquid, and then the premixed liquid and propylene glycol are stirred and mixed to obtain a mixed liquid, and then zinc salt, indium salt and thioacetamide are added to the mixed liquid in sequence while stirring and ultrasonically mixed; the stirring and mixing time is preferably 30 minutes.

[0053] In the present invention, the combination reaction is preferably carried out in an oil bath; the temperature of the combination reaction is preferably 75-85°C, specifically 77°C, 80°C or 83°C, and the insulation reaction time is preferably 1.5-2.5h, specifically 1.8h, 2h or 2.2h.

[0054] In the present invention, after the chemical reaction, the product obtained is preferably purified and then dried; the purification is preferably: dissolving the product obtained in ethanol to obtain a solution, and then centrifuging the solution; the number of purifications is preferably more than 3 times; the drying is preferably vacuum drying; the drying temperature is preferably 55-65°C, specifically 60°C, the vacuum degree is preferably 130-135Pa, specifically 133Pa, and the heat preservation and drying time is preferably 20-30h, specifically 24h.

[0055] The present invention also provides the use of the Z-type heterojunction semiconductor material described in the above scheme or the Z-type heterojunction semiconductor material obtained by the preparation method described in the above scheme as a piezoelectric photocatalyst.

[0056] In the present invention, the application preferably includes the following steps: adding a Z-type heterojunction semiconductor material to a reaction system to be catalyzed under ultrasonic conditions to carry out a piezoelectric photocatalytic reaction.

[0057] The Z-type heterojunction semiconductor material provided by the present invention has good photogenerated charge separation capability and transmission efficiency, high photocatalytic activity, can be used as a piezoelectric photocatalyst, and has broad application prospects.

[0058] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0059] Example 1

[0060] (1) Titanium dioxide and barium hydroxide octahydrate were mixed in a mass ratio of 8:190, 10 mL of deionized water was added, and the mass ratio of titanium dioxide to water was 8:1000. The mixture was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 200° C. for 48 h. The obtained product was washed with hydrochloric acid and deionized water until the pH value was neutral, and vacuum dried at 60° C. to obtain BaTiO3 (barium titanate).

[0061] (2) The BaTiO3 and sodium borohydride were mixed in a mass ratio of 2:3, calcined in a tube furnace at 425°C under nitrogen protection for 2 h, washed with deionized water and ethanol three times, and dried to obtain BaTiO 3-x .

[0062] (3) 0.1 g of BaTiO 3-x Dissolve in 32 mL of deionized water (pH 2.5) to obtain a premixed solution, and then add 8 mL of glycerol to the premixed solution. 3-xThe mass ratio of zinc chloride, indium trichloride tetrahydrate and thioacetamide is 100:272:586:300, and the mixture is stirred for 30 minutes to obtain a mixture; the mixture is ultrasonicated for 15 minutes, and then put into an oil bath pot, and reacted at 80°C for 2 hours. The obtained product is centrifuged with ethanol for 3 times, and vacuum dried at 60°C for 24 hours to obtain a Z-type heterojunction semiconductor material, which is recorded as BaTiO 3-x @ZnIn2S4.

[0063] (4) An ultrasonic cleaner was used as a mechanical energy input source to evaluate the piezoelectric catalytic reduction effect of Z-type heterojunction semiconductor materials. The specific method is as follows: 50 mg of Z-type heterojunction semiconductor material was dispersed into 50 mL of 5 mg / L tetracycline aqueous solution to obtain a suspension; before ultrasonic vibration, the suspension was stirred for 30 min to achieve adsorption-desorption equilibrium; a 300 W xenon lamp was added with a filter (λ ≥ 420 nm) as a simulated visible light source, the light source was turned on, and the beaker containing 50 mL of the suspension was fixed in a specific position of the ultrasonic cleaner (where it can be exposed to light and ultrasonic vibration at the same time), and a piezoelectric photocatalytic reduction test was performed under the synergistic effect of light and ultrasonic vibration; 2 mL of the reaction solution was taken out every 15 min, and during the reaction, it was filtered with a disposable 0.45 μm filter and analyzed using a high performance liquid chromatograph (UlitiMate 3000, Thermo Scientific, USA) was used to test the degradation of BPA; a C18 chromatographic column (5μm, 4.6×250mm, Agilent Technologies) was used, chromatographic grade acetonitrile and ultrapure water were used as the mobile phase (acetonitrile: ultrapure water = 60:40 (V / V)), the flow rate was 1mL / min, the detection wavelength was 357nm, the single injection volume was 20μL, the temperature was 25°C, and the absorption peak was determined by liquid chromatography (HPLC). In order to exclude the effects of Z-type heterojunction semiconductor material adsorption, light irradiation and ultrasonic vibration on the degradation effect of U(VI), the adsorption experiment of Z-type heterojunction semiconductor material on U(VI) solution in a dark environment and the blank control experiment with only light irradiation or ultrasonic vibration without a catalyst were carried out respectively. The degradation rate of U(VI) is calculated using formula I:

[0064]

[0065] In formula I, η is the degradation rate, C0 represents the initial concentration of the pollutant, and C t Represents the concentration of pollutants.

[0066] The test results of the piezoelectric catalytic reduction effect of Z-type heterojunction semiconductor materials showed that the degradation rate of tetracycline was 86.42%.

[0067] Example 2

[0068] (1) Titanium dioxide and barium hydroxide octahydrate were mixed in a mass ratio of 8:190, 10 mL of deionized water was added, and the mass ratio of titanium dioxide to water was 8:1200. The mixture was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 180° C. for 48 h. The obtained product was washed with hydrochloric acid and deionized water until the pH value was neutral, and dried in vacuum at 70° C. to obtain BaTiO3 (barium titanate).

[0069] (2) The BaTiO3 and sodium borohydride were mixed in a mass ratio of 2:4, calcined in a tube furnace at 450°C under nitrogen protection for 2.5 hours, washed with deionized water and ethanol three times, and dried to obtain BaTiO 3-x .

[0070] (3) 0.1 g of BaTiO 3-x Dissolve in 32 mL of deionized water (pH 2.5) to obtain a premixed solution, and then add 8 mL of glycerol to the premixed solution. 3-x The mass ratio of zinc chloride, indium trichloride tetrahydrate and thioacetamide is 100:272:586:300, and the mixture is stirred for 40 minutes to obtain a mixture; the mixture is ultrasonicated for 15 minutes, and then placed in an oil bath pot, and reacted at 85°C for 2 hours. The obtained product is centrifuged with ethanol for 3 times, and vacuum dried at 70°C for 24 hours to obtain a Z-type heterojunction semiconductor material, which is recorded as BaTiO 3-x @ZnIn2S4.

[0071] Performance Testing

[0072] The BaTiO of Example 1 3-x SEM test was performed, and the results were as follows Figure 1 As shown. Figure 1 It can be seen that BaTiO 3-x It has a polyhedral structure with a larger specific surface area, which can improve the catalytic performance of the material.

[0073] The Z-type heterojunction semiconductor material of Example 1 was subjected to SEM testing, and the results are as follows: Figure 2 As shown. Figure 2 It can be seen that the Z-type heterojunction semiconductor material prepared by the present invention is a nanosheet structure.

[0074] The BaTiO prepared in Example 1 was analyzed by electron spin resonance spectrometer. 3-x Structural testing was performed and the results were as follows Figure 3 As shown. Figure 3It can be seen that there are strong characteristic peak signals in the figure, proving that there are oxygen vacancies (OVs) on the surface of BaTiO3. OVs can serve as a conduction channel for electrons, improving the catalytic performance of the material. When BaTiO3 is deformed by external force along the asymmetric direction of its structure, polarization will occur inside it, generating positive and negative charges on the relative surfaces. The formed built-in electric field can drive the separation of photogenerated electrons and holes, reduce their recombination rate, and improve the piezoelectric catalytic efficiency. Among them, oxygen vacancies (OVs) with abundant localized electrons can be used as reaction sites to regulate the charge density distribution, thereby enhancing the adsorption and activation of O2 and reducing the energy barrier for O2 reduction. OVs on BaTiO3 can effectively enhance the adsorption of O2 and capture more free electrons, thereby promoting the activation of O2 to ·O2 - Due to the mutual promotion of oxidation and reduction reactions, the enhancement of the O2 activation process is conducive to the improvement of the overall reaction rate.

[0075] The BaTiO of Example 1 3-x , ZnIn2S4 and BaTiO 3-x @ZnIn2S4 was tested by XRD, and the results are as follows Figure 4 As shown. Figure 4 It can be seen that the diffraction peaks at 21.51, 27.76, 47.52, 52.38 and 55.85° in the XRD spectrum of ZnIn2S4 correspond to the (006), (102), (110), (116) and (022) crystal planes of the hexagonal phase ZnIn2S4, respectively; for BaTiO 3-x XRD spectrum, all the diffraction peaks are attributed to the tetragonal BaTiO 3-x ;BaTiO 3-x The eight diffraction peaks at 22.28, 31.61, 38.98, 45.15, 51.20, 56.06, 65.96 and 74.88° are respectively attributed to its (100), (110), (111), (200), (210)(211), (220) and (310) crystal planes. 3-x The diffraction peaks of the ZnIn2S4 composite material are composed of hexagonal ZnIn2S4 and tetragonal BaTiO 3-x composition, and no other impurity peaks, indicating that the composite material prepared by the present invention is completely BaTiO 3-x @ZnIn2S4, does not contain other impurities.

[0076] The piezoelectric catalytic degradation ability of tetracycline solution was tested under three different test conditions: Z-type heterojunction semiconductor material + ultrasonic vibration, Z-type heterojunction semiconductor material only, and ultrasonic vibration only, to further demonstrate the important role of piezoelectric effect in piezoelectric catalysis. The results are shown in Figure 5 As shown. Figure 5It can be seen that when the piezoelectric material is subjected to ultrasonic vibration, it can show excellent piezoelectric catalytic performance. The degradation rate of tetracycline by the Z-type heterojunction semiconductor material is 97.62%, while the degradation rate of tetracycline is 86.42% when there is only light irradiation, and the degradation rate of tetracycline is the lowest at 76.59% when there is only ultrasonic vibration. This confirms the important role of the piezoelectric effect in the photocatalytic degradation process.

[0077] It can be seen from the above embodiments that the Z-type heterojunction semiconductor material provided by the present invention greatly improves the separation and migration rate of photogenerated carriers, realizes the spatial separation of redox sites, and improves the BaTiO 3-x The extraction rate of photogenerated holes accelerates the catalytic reaction rate of surface photoredox.

[0078] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A Z-type heterojunction semiconductor material, characterized in that: Including BaTiO 3-x and coated on the BaTiO 3-x The surface of ZnIn2S4; the BaTiO 3-x Forming a heterojunction structure with ZnIn2S4; the BaTiO 3-x The value range of x is 0.001~0.

045.

2. The Z-type heterojunction semiconductor material according to claim 1, characterized in that: The value range of x is 0.005 to 0.

040.

3. The Z-type heterojunction semiconductor material according to claim 1, characterized in that: The ZnIn2S4 and BaTiO 3-x The molar ratio is 12 to 15:

1.

4. The Z-type heterojunction semiconductor material according to claim 1 or 3, characterized in that: The particle size of the ZnIn2S4 is 500-700 nm, and the BaTiO 3-x The particle size is 100~300nm.

5. The method for preparing the Z-type heterojunction semiconductor material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) BaTiO3 and sodium borohydride are mixed and calcined in a protective atmosphere to obtain BaTiO 3-x ; (2) The BaTiO 3-x The Z-type heterojunction semiconductor material is obtained by mixing with glycerol, zinc salt, indium salt, thioacetamide and water for chemical reaction.

6. The preparation method according to claim 5, characterized in that: The calcination temperature is 400-500° C., and the heat preservation calcination time is 1.5-3 hours.

7. The preparation method according to claim 5, characterized in that: The BaTiO 3-x The molar ratio of Ba to zinc in the zinc salt is 15-17:100; The BaTiO 3-x The molar ratio of Ba to indium in the indium salt is 8:54-65; The BaTiO 3-x The mass ratio of thioacetamide to 1:2-3.

8. The preparation method according to claim 5 or 7, characterized in that: The chemical reaction is carried out in an oil bath; The temperature of the chemical combination reaction is 70-90° C., and the heat preservation reaction time is 1-3 hours.

9. Use of the Z-type heterojunction semiconductor material according to any one of claims 1 to 4 or the Z-type heterojunction semiconductor material obtained by the preparation method according to any one of claims 5 to 8 as a piezoelectric photocatalyst.

10. The use according to claim 9, characterized in that: The application comprises the following steps: under ultrasonic conditions, adding a Z-type heterojunction semiconductor material into a reaction system to be catalyzed to carry out a piezoelectric photocatalytic reaction.